Purification of heat-labile enterotoxin from four Escherichia coli strains by affinity immunoadsorbent: evidence for similar subunit structure. - Dafni, Z (1978)
A single-step method for the purification of heat-labile enterotoxin of Escherichia coli is described. The method involves an affinity immunoadsorbent made with antiserum to cholera toxin. Crude toxin preparations of three human and one porcine enterotoxinogenic strains of E. coli were purified on this immunoadsorbent, and the elution products suggest that the toxin molecule is composed of subunits. One kind of subunit shared by these four strains showed similar mobility of sodium dodecyl sulfate-polyacrylamide gel electrophoresis, close antigenic relationship, and an antigen in common with cholera enterotoxin.